Development of Specific DNA Barcodes for the Dinophyceae Family Kareniaceae and Their Application in the South China Sea - Zhang, Weiqian; Zhang, Qingchun; Smith, Kirsty F.; Qiu, Limei; Liu, Chao; Yin, Xiaoting; Liu, Qing (Frontiers in Marine Science, 2022)
Species from the family Kareniaceae (Dinophyceae) frequently cause harmful algal blooms (HABs), with serious ecological impacts and risks to human safety and aquaculture activities in coastal waters worldwide. However, due to their small size, lack of morphological divergence, and low abundance during non-bloom periods, the diversity within this family is not well understood. By comparing the commonly used molecular markers, the Internal Transcribed Spacer (ITS) region was found to have an appropriate mutation rate to distinguish three of the most common genera (Karenia, Karlodinium, and Takayama) within the Kareniaceae family and different geographical strains of Kareniaceae. Specific primers targeting the ITS region of Karenia, and the other primers specific to the genera Karlodinium and Takayama, were designed. Specificity of the primers was tested using 17 strains of Kareniaceae species and 15 non-target species. Representative Kareniaceae species could be successfully detected even at low concentrations of target DNA template with a limit of detection of 3.2 pg. The primers were also assessed using high-throughput sequencing with two environmental samples from the South China Sea (SCS). Analysis of the reads identified as Kareniaceae species revealed a high diversity and the existence of unreported Kareniaceae species in the SCS. In conclusion, the newly developed molecular barcodes specifically detected Kareniaceae species in the field and will provide technical support for the effective warning and monitoring of Kareniaceae HABs.